A comparative study on hybrid power-to-liquids/power-to-gas processes coupled with different water electrolysis technologies - Gao, Ruxing; Zhang, Leiyu; Wang, Lei; Zhang, Xiudong; Zhang, Chundong; Jun, Ki Won; Ki Kim, Seok; Park, Hae Gu; Gao, Ying; Zhu, Yuezhao; Zhao, Tiansheng; Wan, Hui; et al. (Energy Conversion and Management, 2022)
Recently, Power-to-Liquids (PTL) and Power-to-Gas (PTG) processes have been attracting extensive attentions as carbon-neutral technologies because they transform wasted CO2 into sustainable liquid fuels and synthetic natural gas, meanwhile storing the excess and intermittent renewable energies into stable chemical energies. In both PTL and PTG processes, hydrogen production is a key step, which can be achieved by using different water electrolysis technologies, such as alkaline water electrolysis (AWE), anion exchange membrane electrolysis (AEM), proton exchange membrane electrolysis (PEM) and solid oxide electrolysis (SOEC). In this work, to implement a systematic comparison of the effects of different water electrolysis technologies on the technical performances of the PTL/PTG hybrid process, we proposed four PTL/PTG hybrid process cases coupled with the aforementioned water electrolysis technologies, and conducted a detailed comparative technical analysis in terms of energy efficiency, carbon efficiency, net CO2 reduction rate and exergy efficiency. The results revealed that all the proposed process cases can be considered as essential candidate technologies for CO2 transformation, and the PTL/PTG hybrid process combined with SOEC is more competitive in terms of energy and exergy efficiencies, whereas that combined with AEM shows higher carbon efficiency and net CO2 reduction rate. Moreover, we also compared the process performances of the PTL/PTG hybrid processes combined with SOEC via the direct and indirect routes. It seems that both the indirect and direct ones are comparable in energy and exergy efficiencies. However, the direct one benefits CO2 mitigation, while, the indirect one favors syncrude production.
Keywords: Hybrid process; Liquid power; Membrane electrolysis; Power; Power-to-gas; Power-to-liquid; Process-models; Technical comparison; Water electrolysis; Power-to-gas; Power-to-liquids; Process modelling; Technical comparison; Water electrolysis